Analisis Sistem Pembayaran Kredit di KSP Kopdit Swasti Sari Cabang Atambua Menggunakan Persamaan Beda Linear Orde Satu - Agustinus Mario Bere; Faustianus Luan; Leonardus Frengky Obe (Saintek Lahan Kering, 2023)
ABSTRACT Giving credit is a business activity that contains a high risk and affects the sustainability of businesses such as cooperatives and banking. The aims of this research are to: (a) knowing the credit decision making system implemented in KSP Kopdit Swasti Sari, (b) knowing the calculation of the remaining credit payments using the first-order linear difference equation. In this study, the method used to calculate the remaining debt for credit payments is a first-order linear difference equation, namely the remaining debt after the first payment is the same as the remaining debt after payment to t plus interest minus annuity. The results of this study indicate that the credit decision-making process is considered worthy of receiving a credit loan if it meets the requirements that have been set at the KSP Kopdit Swasti Sari. The step to calculate the remaining credit payments using a mathematical model is to find the amount of fixed installments from an ordinary annuity with a different loan size, namely Rp 5.000.000, Rp 10.000.000 and Rp 15.000.000. After getting the results from the ordinary annuity, a mathematical model of the remaining credit payments is formed using equation (2.13). The results of the calculation of the remaining credit payments using a mathematical model are as follows: For the first order linear difference equation with a loan size of Rp 5.000.000 after paying the first installment () the remaining debt is Rp 4.900.081 and the remaining debt () of Rp. 8. For a large loan of Rp. 10.000.000 after paying the first installment () the remaining debt is Rp. 9.800.162 and on payment of () the remaining debt is Rp. 16. For a large loan of Rp 15.000.000 after paying the first installment () the remaining debt is Rp 14.700.243 and on payment of () the remaining debt is Rp 24.